Where the bluebird sings to the lemonade springs living and writing in the West - Stegner, Wallace 1909-1993 (Penguin Books, 1993)
The author's essays on the West and his admiration of other writers.
Keywords: Stegner, Wallace <1909-1993> -- Homes and haunts -- West (U.S.); Stegner, Wallace -- 1909-1993; Geschichte 1900-2000; Authors, American -- Homes and haunts -- West (U.S.); Authors, American -- 20th century -- Biography; Haus; Autobiografie; West (U.S.) -- In literature; West (U.S.) -- Intellectual life -- 20th century; USA -- Weststaaten; Biografie